Absolute Asymmetric Catalysis, from Concept to Experiment: A Narrative - Crusats, Joaquim; Moyano, Albert (Synlett, 2021)
The generally accepted hypothesis to explain the origin of biological homochirality (that is to say, the fact that proteinogenic amino acids are left-handed, and carbohydrates right-handed, in all living beings) is to assume, in the course of prebiotic chemical evolution, the appearance of an initial enantiomeric excess in a set of chiral molecular entities by spontaneous mirror-symmetry breaking (SMSB), together with suitable amplification and replication mechanisms that overcome the thermodynamic drive to racemization. However, the achievement of SMSB in chemical reactions taking place in solution requires highly specific reaction networks showing nonlinear dynamics based on enantioselective autocatalysis, and examples of its experimental realization are very rare. On the other hand, emergence of net supramolecular chirality by SMSB in the self-assembly of achiral molecules has been seen to occur in several instances, and the chirality sign of the resulting supramolecular system can be controlled by the action of macroscopic chiral forces. These considerations led us to propose a new mechanism for the generation of net chirality in molecular systems, in which the SMSB takes place in the formation of chiral supramolecular dissipative structures from achiral monomers, leading to asymmetric imbalances in their composition that are subsequently transferred to a standard enantioselective catalytic reaction, dodging in this way the highly limiting requirement of finding suitable reactions in solution that show enantioselective autocatalysis. We propose the name ‘absolute asymmetric catalysis’ for this approach, in which an achiral monomer is converted into a nonracemic chiral aggregate that is generated with SMSB and that is catalytically active.Our aim in this Account is to present a step-by-step narrative of the conceptual and experimental development of this hitherto unregarded, but prebiotically plausible, mechanism for the emergence of net chirality in molecular reactions.1 Introduction: The Origin of Biological Homochirality and Spontaneous Mirror-Symmetry Breaking2 Experimental Chemical Models for Spontaneous Mirror-Symmetry Breaking: The Soai Reaction and Beyond3 Spontaneous Mirror-Symmetry Breaking in Supramolecular Chemistry: Plenty of Room at the Top4 Absolute Asymmetric Catalysis: An Alternative Mechanism for the Emergence of Net Chirality in Molecular Systems 5 Experimental Realization of Top-Down Chirality Transfer to the Molecular Level6 Conclusions and Outlook
Keywords: absolute asymmetric catalysis; autocatalysis; biological homochirality; dissipative systems; spontaneous mirror-symmetry breaking; supramolecular catalysis; systems chemistry